RANCANG BANGUN SISTEM KENDALI KELISTRIKAN MASJID AL-ISTIQOMAH MENGGUNAKAN PENERIMA HC-12 BERBASIS ARDUINO - Febriansyah Putra; Ali Hanafiah Rambe; Lisa Adriana Siregar (Universitas Harapan Medan, 2022)
The current development of control and automatic system technology allows operators to easily turn on and off electronic devices remotely without having to make direct contact, this is very effective in saving time and helping one's work become easier. Currently electrical energy is a basic human need. However, the use of electrical energy is not used optimally, its use tends to be excessive, the cause is due to someone's negligence of an electrical device that forgot to turn it off. To overcome this problem, it is necessary to have an automatic control system that can control the switch to help minimize the waste of electrical energy. However, various kinds of automatic control system devices have drawbacks, including requiring an internet connection or using an SMS gateway so that they can be controlled remotely, which will increase spending on the budget for internet or credit needs every month. The method used in this design uses Arduino uno, HC – 12 module, ZMTC103C current sensor, and relay. This tool works when an instruction signal is received via the HC-12 module then the signal is forwarded to Arduino to turn on or turn off the electric device through a relay, the current sensor detects the condition of the electric device. From the results of testing the control system successfully turns on and off loads in the form of lights, fans, water pumps properly and can detect lights that go out.